Enhanced Hetero‐Junction Quality and Performance of Kesterite Solar Cells by Aluminum Hydroxide Nanolayers and Efficiency Limitation Revealed by Atomic‐resolution Scanning Transmission Electron Microscopy. Issue 2 (13th December 2018) - Xie, Haibing; Sánchez, Yudania; Tang, Pengyi; Espíndola‐Rodríguez, Moisés; Guc, Maxim; Calvo‐Barrio, Lorenzo; López‐Marino, Simon; Liu, Yu; Morante, Joan R.; Cabot, Andreu; Izquierdo‐Roca, Victor; Arbiol, Jordi; et al.
Abstract : A strategy for interface engineering of hetero‐junctions in kesterite solar cells by using Al(OH)3 is demonstrated. The hydroxide nanolayers are prepared via a facile and fast wet chemical route, based on an aqueous solution of aluminum chlorides and thioacetamide. Considerable enhancement of open circuit voltage ( V oc ) (30–60 mV) and fill factor (FF) (10–20%) after this chemical treatment are observed, achieving a champion conversion efficiency of 9.1% and a champion FF of 70% (among the best FF in kesterite solar cells). The functional mechanism is systematically studied by current‐voltage, capacitance‐voltage, temperature dependence of current–voltage and photoluminescence measurements, which reveal that Al(OH)3 nanolayers can effectively reduce the interface recombination and largely improve the shunt resistance. Furthermore, atomic resolution high angle annular dark field scanning transmission electron microscopy (HAADF‐STEM) evidences the epitaxial relationship of Al(OH)3 with kesterite and CdS, indicating the benign and effective interface passivation achieved by this chemical treatment. Finally, based on HAADF‐STEM and electron energy loss spectroscopy mappings, insights into the efficiency limiting and beneficial factors for CZTSSe solar cells, as well as suggestions to further improve both the bulk and related interfaces are presented. Abstract : Al(OH)3 nanolayers are employed for the interface modification of Cu2 ZnSn(S, Se)4 /CdS hetero‐junction of kesterite solar cells. Considerable open circuit voltage and fill factor increment are observed, which is ascribed to reduced interface recombination and shunt paths by an epitaxial relationship of Al(OH)3 with kesterite and CdS.